2020
DOI: 10.3126/nrber.v32i2.35300
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Performance of Nepalese Commercial Banks: Evidence from Panel Data Approach

Abstract: The impact of bank specific factors on the financial performance of Nepalese commercial banks is analyzed in this paper. The financial performance is measured by using return on assets (ROA). Similarly, managerial efficiency (ME), liquidity (LIQ), credit risk (CR), assets quality (AQ) and operational efficiency (OE) is used as proxy of bank specific factors. This study used panel data of 17 commercial banks for the period of 2010/11 to 2017/18. Breusch and Pagan Lagrangian multiplier test showed that Pooled Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…The outcome shows a positive relationship between liquidity and the return on assets of the financial institution. which are aligned with the studies of Almaqtari et al (2018) and Shrestha et al (2020). while the ratio of deposits displays a negative association with the return on assets of the financial institution, which is consistent with Al-Homaidi, E. A.…”
Section: Correlation Matrixessupporting
confidence: 90%
See 2 more Smart Citations
“…The outcome shows a positive relationship between liquidity and the return on assets of the financial institution. which are aligned with the studies of Almaqtari et al (2018) and Shrestha et al (2020). while the ratio of deposits displays a negative association with the return on assets of the financial institution, which is consistent with Al-Homaidi, E. A.…”
Section: Correlation Matrixessupporting
confidence: 90%
“…The findings of this study on internal factors revealed that the success of commercial banks in Afghanistan was positively affected by liquidity and asset management. The finding was emphasized in many previous studies (Shrestha, 2020;Al-Homaidi et al, 2020;Masood, Yahya, et al, 2017;Ashraf & Ashraf, 2012). However, the results contradict some other studies (Rani & Zergaw, 2017;Naderi, 2021) that found a negative impact of liquidity on bank profitability.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accounting measures is used to represent firm performance (Antle & Smith, 1986;Lambert & Larcker, 1987;Raithatha & Komera, 2016)). Following (Murphy,1985;Jensen and Murphy 1990;Gibbons and Murphy, 1990;Raithatha & Komera, 2016), (Sheikh et al, 2018), (Shrestha, 2020)return on equity (ROE) and ROA are used as the accounting based measures of firm performance. Further, firm specific variables such as size, leverage, and risk are considered as control variables, they could influence the pay-performance relationship.…”
Section: Methodsmentioning
confidence: 99%
“…In the Nepalese context, Gautam [32] verified the positive role of management efficiency, capital adequacy, and GDP and the negative role of liquidity management and asset quality in determining financial performance. Furthermore, Shrestha [33] observed that financial risk had the opposite influence on the success of banks in the Nepalese environment, while asset quality, management effectiveness, and operational effectiveness had a positive influence. Similarly, Gwachha [34] discovered a robust positive effect of the size of assets, deposit ratio, market size, and interest rate on the performance of banks and a significant adverse effect on loans portfolio.…”
Section: Introductionmentioning
confidence: 99%